Pterostilbene down‐regulates hTERT at physiological concentrations in breast cancer cells: Potentially through the inhibition of cMyc. Issue 4 (26th December 2017) - Daniel, Michael; Tollefsbol, Trygve O.
Abstract: Human telomerase reverse transcriptase ( hTERT ) encodes the catalytic subunit of telomerase, which has been shown to be upregulated in many cancers. Pterostilbene is a naturally occurring stilbenoid and phytoalexin found primarily in blueberries that exhibits antioxidant activity and inhibits the growth of various cancer cell types. Therefore, the aim of this study was to determine whether treatment with pterostilbene, at physiologically achievable concentrations, can inhibit the proliferation of breast cancer cells and down‐regulate the expression of hTERT . We found that pterostilbene inhibits the cellular proliferation of MCF‐7 and MDA‐MB‐231 breast cancer cells in both a time‐ and dose‐dependent manner, without significant toxicity to the MCF10A control cells. Pterostilbene was also shown to increase apoptosis in both breast cancer cell lines. Dose‐dependent cell cycle arrest in G1 and G2/M phase was observed after treatment with pterostilbene in MCF‐7 and MDA‐231 cells, respectively. hTERT expression was down‐regulated after treatment in both a time‐ and dose‐dependent manner. Pterostilbene also reduced telomerase levels in both cell lines in a dose‐dependent manner. Moreover, cMyc, a proposed target of the pterostilbene‐mediated inhibition of hTERT, was down‐regulated both transcriptionally and posttranscriptionally after treatment. Collectively, these findings highlight a promising use of pterostilbene as a natural, preventive, and therapeutic agent against the development and progression of breast cancer. Abstract : Effect of pterostilbene on colony forming potential. A clonogenic assay was performed to evaluate the long‐term effects of pterostilbene on MCF‐7 and MDA‐MB‐231 breast cancer cells. After treatment, pterostilbene was shown to inhibit the colony forming potential of both MCF‐7 and MDA‐MB‐231 cells in a dose‐dependent manner. No notable inhibition was seen in MCF10A control cells, when compared to the cancer lines.